Growth Performance of Broiler Chicken as Affected by Phased Feed Restriction and Fat Supplementation - Malpotra, Kunal; Singh, Udeybir; Sethi, A.P.S.; Singh, Parminder; Hundal, J. S. (Indian Journal of Animal Nutrition, 2017)
A study was conducted to find out the effects of feed restriction and additional (1%) fat supplementation on growth performance of broiler chicken. A total of 480 chicks were distributed randomly into8 groups having total 60 birds per treatment with 4 replicates having 15 chicks in each replicate. The treatments consisted of T0- control group fed ad lib. as per ICAR (2013) specification i.e. starter diet contained 22% CP and 3000 kcal/kg ME, grower diet contained 21.5% CP and 3050 kcal ME/kg and finisher diet contained 19.5% CP and 3100 kcal ME/kg), T1- T0 with additional 1% fat supplementation,T2- T0 with feed restriction at 8-14 days of age (DOA) (8-10 h), T3- T1 with feed restriction at 8-14 DOA (8-10 h), T4- T0 with feed restriction at 15-21 DOA (8-10 h), T5- T1 with feed restriction at 15-21 DOA (8-10 h), T6- T0 with feed restriction at 22-28 DOA (8-10 h) and T7-T1 with feed restriction at 22-28 DOA (8-10 h). The feed intake was lower in chicken at 2nd, 3rd and 4th week feed restricted groups as compared to control. Additional fat supplementation reduced feed intake at 3rd week of age. There was reduction (P